S̱iva Kumāra - Brahamajagadīs̱a Siṅgha (Vārisa S̱āha Fāuṇḍes̱ana, 2010)
Study on the works of Shiv Kumar, 1937-1973, Panjabi poet
Includes bibliographical references (p. 128). - Panjabi in Gurmukhi-Schr
Keywords: Shiv Kumar 1937-1973